HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN KESIAPAN MENGHADAPI MENARCHE PADA SISWI KELAS VII DI SMP 1 PLAYEN GUNUNGKIDUL - Ayu, Suci Musvita; Djannah, Sitti Nur; Wardani, Yuniar (Universitas Ahmad Dahlan, 2010)
Background: Adolescent is a periode where many physical changes and environmental demainds occurings. For a girl, the most visible changes is the beginning of menarche or first menstruation. Because menarche is definitely happened to every girl. Its necessary for a girl to have many sources of social support to help her reduce anxiety during her menarche periode and decrease her readiness on that situasion. The goal is to find of relationship between social support and readiness on menarche at VII grade of SMP 1 Playen Gunungkidul. Method: This was an analytical observation research using cross sectional approach. The research subjects were 26 students of VII grade of SMP 1 Playen, 12-13 years old and having menarche. Sampel were taken using accidental sampling techniques, data analysis used Chi Square. Result : There was relationship between social support and readiness on menarche with correlation coefficient was 0,599 and significance/Asymp. Sig was 0,006 which compared by a= 0,05 so P value < 0,05. from 26 subjects, 65,4 persen had sufficient social support level and 73 persen subjects had sufficient level of readiness on menarche. Conclusion : There was relationship between social support and readiness on menarche at VII grade of SMP 1 Playen Gunungkidul Yogyakarta andd readiness on menarche. 65,4 persen had sufficient social support level and 73 persen subjects had sufficient level of readiness on menarche. Key Word: Social Support, Readiness On Menarche, Student